Physiological changes associated with the appearance of slow variants in cultures of Streptococcus lactis : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Microbiology at Massey University, New Zealand - Skipper, Nigel Armstrong (Massey University, 1972)
Streptococcus lactis C10 Slow, a variant of the normal 'fast' strain of S.lactis C10, was only capable of rapid and extensive growth in skim milk if casein hydrolysates were added. It was postulated, therefore, that the slow variant is defectively proteolytic. A sensitive assay of proteolysis, based on the release of radio-activity from iodinated casein, was developed, checked for usefulness with known proteinases, then used to assay the streptococcal enzymes. Fractionation of the two strains, by either mechanical cell disruption and differential centrifugation or by cell-wall digestion with a muraminidase, established that most of the cell-bound proteinases of the parent strain were surface-bound. This activity was virtually absent in the slow variant. Partial characterization of the surface-proteinase(s) showed that maximum activity was exhibited at pH 6.0-6.8, in 0.05 M phosphate buffer, at 30-32°C. It was rapidly inactivated at 37°C, both when cell-bound and when free of the cells. Examination of a second pair of strains, S.lactis H1 Fast and S.lactis H1 Slow, indicated a difference in proteinase activity and localization similar to that found between the two S.lactis C10 strains. It was concluded, on the basis of both nutritional evidence and enzymatic analyses, that the slow variant of S.lactis C10 is limited in skim milk by the supply of amino acids and that this is due to a defective surface-bound proteolytic activity.
Keywords: Lactococcus lactis